Preperation for Learning Towards Normal Era - Luki Adam Bahtiar; Sri Rahayu Pudjiastuti; Andayani Ratnaningrum; Armelia Prakasa; Nurdin Nurdin (UIN Sunan Gunung Djati Bandung, 2021)
This paper is devoted to the Preparation for Learning Towards Normal Era. It's been 18 months during the COVID-19 pandemic, there are many ways that educational institutions have done to keep learning going, such as implementing online learning and offline learning. Now it's no longer about thinking about the effectiveness or ineffectiveness of learning both online and offline, everyone has to think about how to prepare for normal learning to return to the way it was before covid 19. This research is a literature study with a qualitative approach with a descriptive method. The results of the study found that the implementation of the normal era in Indonesia reaped many pros and cons how not many people urged that the implementation of the normal era be carried out immediately but in its implementation it needed a mature plan. The joint decision of the four ministers provides a bright spot and hope for educational institutions to implement normal learning. Of course, there are many considerations and policies that must be taken in carrying out normal learning again. Because the conditions of one area with other areas are different. If the condition of the area is included in the green zone, it can carry out learning activities in the classroom. The government gives time for schools to prepare health protocol facilities at schools, such as hand washing stations, hand sanitizers, classroom arrangements, spraying disinfectants, as well as scheduling teaching and learning activities.